Electrodeposition of honeycomb-shaped NiCo2O4 on carbon cloth as binder-free electrode for asymmetric electrochemical capacitor with high energy density. Issue 44 (15th April 2016) - An, Yufeng; Hu, Zhongai; Guo, Bingshu; An, Ning; Zhang, Yadi; Li, Zhimin; Yang, Yuying; Wu, Hongying
Abstract : Through the matching of the honeycomb-shaped NiCo2 O4 /CC (HSNC) and reduced graphene oxide/carbon cloth (rGO/CC) to obtain the binder-free asymmetric electrochemical capacitor with high energy density good rate capability and excellent cycle life. Abstract : Combining high-capacitive metal oxides and excellent conductive carbon substrates is a very significant strategy to achieve high-performance electrodes for electrochemical capacitors (ECs). Herein, the bimetallic (Ni, Co) hydroxide is uniformly grown on the electro-etched carbon cloth (CC) by a facile co-electrodeposition method, and then the honeycomb-shaped NiCo2 O4 /CC (HSNC) composite is formed by transforming the hydroxide precursor into its bimetallic oxides through the subsequent thermal treatment. The special structure of the HSNC as binder-free electrode is responsible for its excellent electrochemical performance with carbon-like power feature. The experimental results show that HSNC electrode exhibits a high specific capacitance with remarkable cycle stability (94.3% after 10 000 cycles at 10 A g −1 ) in the three-electrode configuration. To evaluate further the capacitive performance of the as-prepared binder-free electrode in a full cell set-up, an asymmetric electrochemical capacitor (AEC) is assembled by using the HSNC as the positive electrode and reduced graphene oxide/carbon cloth (rGO/CC) as the negative electrode in KOH electrolyte. The as-assembled device presents an energy density as high as 32.4 W h kg −1 along with power density of 0.75 kW kg −1, comparing with nickel-metal hyoride battery (Ni-MH) batteries (30.0 W h kg −1 at 0.35 kW kg −1 ). Even at the power density of 37.7 kW kg −1 (50-time increase, a full charge–discharge within 3.5 s), energy density still holds at 17.8 W h kg −1, indicating an outstanding rate capability. Furthermore, the as-fabricated device exhibits a long cycle lifetime (76.5% after 10 000 cycles at 3 A g −1 ) with a cell voltage of 1.5 V.